Copper, lead and cadmium removal by Ca Al layered double hydroxides - Rojas Delgado, Ricardo (2014)
Layered double hydroxides are increasingly studied as heavy metal scavengers due to their acid/base buffering capacity that leads to hydroxide precipitation. Their intercalation with ligands such as edta also provides active sites for heavy metal chelation to these solids. In this work, both mechanisms are studied in Ca–Al layered double hydroxides (LDHs) with a Friedel's salt layered structure and intercalated with either nitrate (Ca–Al–NO3) or [Ca(edta)]2 − (Ca–Al–[Ca(edta)]). With this aim, the acid–base buffering capacity of these solids was determined and their removal behavior studied as a function of equilibrium concentration and pH. The solids presented high instability, Ca2 + ions being selectively leached at pH values as high as 8. As a consequence, high affinity and large removal capacity of Cu2 +, Cd2 + and Pb2 + were obtained for Ca–Al–NO3 by a hydroxide precipitation mechanism. The removal capacity of Ca–Al–[Ca(edta)] was quite similar, however, a portion of heavy metal ions was solubilized due to [Ca(edta)]2 − release. The heavy metal hydroxides obtained by the Ca–Al LDH removal action produced immobilization at pH values lower than those produced by simple alkalinization.